Carbon based self-supported electrodes for supercapacitors and batteries - Wang, Huanhuan (2019)
Electrochemical energy storage devices based on conducting polymers deliver higher specific capacity compared with carbon-based supercapacitors and superior kinetics compared to metal-based batteries, thus bridging the gap between capacitors and batteries.